Climate-Human Relations in the Çıldır Lake Basin (Ardahan-Kars) - Bağcı, Harun Reşit; Kılıç, Hediye (Fırat Üniversitesi, 2023)
In this study; In the Çıldır Lake Basin, which is located between the Çıldır-Arpaçay districts in the northeast of Turkey, the relations between climate and socioeconomic structure were examined with an applied climatology approach. Purposes of the study are to classify of the basin climate, to determinate of the temporal changes of temperature and precipitation, and to associate them with socioeconomic activities. To that end; fieldworks were carried out and climate classifications were made. With Mann-Kendall trend analysis; the changes and significance levels in parameters such as monthly and annual average, maximum and minimum temperature and precipitation were determined. “Thermo Hygrometric Index” was used to determine the climatic comfort conditions of the basin. Temperature and precipitation distribution maps of the basin were produced with the Lapse Rate method. The average temperature of Çıldır Lake Basin varies between 6 and -8°C. Winters are cold and snowy and summers are short, cool and rainy because of the Siberian origin cP air masses, altitude and continentally. Regarding climatic comfort; July and August are in the “comfortable category”, while the other months are in the “very cold, cold and cool category”. Trend analysis in the region shows a significant increase trend in monthly and annual temperatures and precipitation. This situation in the region changes the vegetation period, agriculture, tourism and transhumance calendar. It is predicted that temperature and precipitation changes in the basin will increase thunderstorms. Therefore; erosion and floods may be triggered because of the heavy rains.

Bu çalışmada; Türkiye’nin kuzeydoğusunda, Çıldır-Arpaçay ilçeleri arasındaki Çıldır Gölü Havzası’nda, iklim ile sosyoekonomik yapı arasındaki ilişkiler uygulamalı klimatoloji yaklaşımıyla incelenmiştir. Çalışmanın amacı; havza ikliminin tasnifi, sıcaklık ve yağışın zamansal değişiminin tespiti ve sosyoekonomik faaliyetlerle ilişkilendirilmesidir. Bu amaçla; arazi çalışmaları gerçekleştirilmiş, iklim sınıflandırmaları yapılmıştır. Mann Kendall trend analizi ile yörenin; aylık ve yıllık ortalama, maksimum ve minimum sıcaklık, yağış gibi parametrelerindeki değişim ve anlamlılık düzeyleri belirlenmiştir. Havzanın klimatik konfor koşullarını belirlemek için “Thermo Hygrometric Index” kullanılmıştır. Lapse Rate yöntemiyle havzanın; sıcaklık, yağış dağılış haritaları üretilmiştir. Çıldır Gölü Havzası’nın ortalama sıcaklığı 6 ve -8? arasında değişim göstermektedir. Sibirya kökenli cP hava kütleleri, yükseklik ve karasallıktan dolayı kışları soğuk ve kar yağışlı, yazları kısa, serin ve yağışlıdır. Klimatik konfor açısından; temmuz ve ağustos ayları “konforlu”, diğer aylar “çok soğuk, soğuk ve serin” kategorilerindedir. Trend analizleri yörede; aylık, yıllık sıcaklıklarda ve yağışta anlamlı artış eğilimi olduğunu göstermektedir. Bu durum yörede; vejetasyon devresini, tarım, turizm ve yaylacılık takvimini değiştirmektedir. Havzada sıcaklık ve yağış değişimlerinin orajları artırması, şiddetli yağışların erozyon ve taşkınları tetiklemesi muhtemeldir.
ÇILDIR GÖLÜ HAVZASI’NDA (ARDAHAN-KARS) İKLİM-İNSAN İLİŞKİLERİ